Needs Analysis: Development of Contextual Approach Learning Tools Based on Local Balinese Wisdom - Wibawa, I Made Citra; I Gede Margunayasa; Ni Wayan Eka Widiastini (Universitas Pendidikan Ganesha, 2023)
Lectures are textual, and students have yet to actively participate in learning activities actively, making learning less meaningful. This research analyses the need for developing contextual approach learning tools based on local Balinese wisdom. This research is survey research. The methods used to collect data are questionnaires, interviews, observation and document study. The instrument used to collect data was a questionnaire sheet. The technique used to analyze data is qualitative descriptive analysis. The research results are, first, that the approach applied in science skills development courses has yet to be effective. Second, one of the difficulties currently experienced by lecturers is that science learning material needs to be connected to the local context or wisdom. Third, lecturers understand the concept of contextual learning, but learning implementation still needs improvement. One of the things that causes learning activities with contextual concepts to be less than optimal is that they need to be integrated or included in the semester lecture plan. Fourth, a contextual approach will have a positive impact that will improve the learning experience. Fifth, using a contextual approach in learning science skills in elementary school helps students understand and apply it to their lives. It was concluded that developing learning tools with a contextual approach based on local wisdom is very important.